2022
DOI: 10.11646/zootaxa.5141.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the genus Pelecocera Meigen, 1822 (Diptera: Syrphidae) from France: taxonomy, ecology and distribution

Abstract: The occurrence and distribution of the various species of the genus Pelecocera Meigen, 1822 (Diptera: Syrphidae) occurring in France are revised and a new species, Pelecocera garrigae Lair & Nève, 2022 sp. nov., is described from Mediterranean France. Distribution and ecological data of the six French species of Pelecocera are provided and an identification key is given to all these species. Sequences of the cytochrome c oxidase subunit I (COI) from all European Pelecocera species support the morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…for the missing data). In the study of Lair et al (2022) , the authors noted that the COI barcodes of Pelecocera pruinosomaculata and P. scaevoides were resolved as intermixed in their tree, with a mean distance of 0.8% between the taxa. This study utilied part of the same sequences used by Lair et al (2022) and uses the same taxon names and also recovers the COI barcodes of mentioned taxa as clustering together (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…for the missing data). In the study of Lair et al (2022) , the authors noted that the COI barcodes of Pelecocera pruinosomaculata and P. scaevoides were resolved as intermixed in their tree, with a mean distance of 0.8% between the taxa. This study utilied part of the same sequences used by Lair et al (2022) and uses the same taxon names and also recovers the COI barcodes of mentioned taxa as clustering together (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the Nearctic region, three other Pelecocera sg. Chamaesyrphus species are listed ( Skevington 2020 Lair et al 2022 , Skevington 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anasimyia Schiner, 1864 (Claussen & Torp, 1980); Brachyopa Meigen, 1822 (Pellmann, 1998); Callicera Panzer, 1809 (Speight, 1991;Smit, 2014); Ceriana Rafinesque, 1815 (van Steenis et al, 2016); Claussenia Vujić & Ståhls, 2013(Vujić et al, 2013; Doros Meigen, 1803 (Speight, 1988);Eumerus Meigen, 1822(Van der Goot, 1968Doczkal, 1996;Speight et al, 2021); Merodon Meigen, 1803 (Vujić et al, 2021;and references therein); Myolepta Newman, 1838 (Reemer et al, 2004); Neocnemodon Goffe, 1944 (Bartsch, 2009); Paragus Latreille, 1804 (Goeldlin de Tiefenau, 1976;Goeldlin de Tiefenau & Lucas, 1981;Marcos-García, 1986;Marcos-García & Rojo, 1994;Sommaggio, 2002); Pelecocera Meigen, 1822(van Eck & Mengual, 2021Lair et al, 2022); and Riponnensia Maibach, Goeldlin de Tiefenau & Speight, 1994 (Claussen, 1991;Bot et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Mengual et al (2015b) synonymized P. lusitanica under Pelecocera (Chamaesyrphus) lugubris Perris, 1839 without studying the type material, but van Eck & Mengual (2021) suggested to use P. lusitanica until a comprehensive molecular study can be carried out using specimens from Northern, Central and Southern Europe, including the Iberian Peninsula. Lair et al (2022) demonstrated that the name for the specimens identified as P. lusitanica from mainland France (all records are from the Atlantic coast) is P. lugubris. Thus, the question about the synonymy proposed by Mengual et al (2015b) remains open and we decided to use P. lusitanica for the studied Corsican specimens as they do not originate from mainland France.…”
Section: Iucn Status -Least Concernmentioning
confidence: 99%
“…Pelecocera ( Pelecocera ) tricincta Meigen, 1822 and Pelecocera ( Chamaesyrphus ) lugubris Perris, 1839 are two of the eight species occurring in Europe [ 4 ]. However, the number of species in Europe remains unclear because a worldwide revision of the genus is needed to resolve all the taxonomic doubts that exist at the species level.…”
Section: Introductionmentioning
confidence: 99%